METHODOLOGICAL APPROACHES AND PRINCIPLES BEFORE PROFESSIONAL SKILLS OF JUNIOR SPECIALIST FUTURE ECONOMIC PROFILE - Гаврутенко, Л. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The theoretical aspects of professional skills of young experts in economics in the study of professional disciplines are considered in the article . The author clarifies the composition of the professional skills of junior specialists in economics and justifies methodological approaches to their formation: competence, systematic and synergetic, personality and activity and integrative